Digital Transformation of Land Certificates in Combating Land Mafia: A Socio-Legal and Empirical Study in Indonesia - Muhammad Yasir; Gunawan Hadi Purwanto (Faculty of Law Universitas Jenderal Soedirman, 2026)
The implementation of electronic land certificates is a fundamental component of the digital transformation of land administration in Indonesia, aimed at increasing transparency, efficiency, and legal certainty. While previous studies often view electronic certificates as merely administrative tools, this study addresses a critical gap by analyzing their socio-legal implications and legal effectiveness in combating land mafia practices. Employing empirical legal research methods with a socio-legal approach, this study leverages in-depth interviews with the Bojonegoro Agrarian Office, law enforcement officers, and rural communities in East Java, as well as field observations. Empirical findings indicate that digitalization has resulted in significant improvements in administrative efficiency, reducing certificate issuance times by approximately 50% and measurably reducing document forgery disputes by 30% between 2022 and 2024. However, digitalization has proven only partially effective: rather than eliminating agrarian crimes, it has altered their modus operandi, creating new vulnerabilities to internal database manipulation and systemic bureaucratic collusion. Furthermore, a structural digital divide and persistent low public trust among rural and elderly demographics critically hinder the program's universal success. This manuscript contributes to the international scholarly discourse on digital land governance by demonstrating that, in developing countries, technological modernization must be strictly accompanied by institutional integrity, strict bureaucratic oversight, and socio-legal inclusiveness to achieve substantive legal certainty.